Effect of Dynamically Recrystallized Grains on Rare Earth Texture in Magnesium Alloy Extruded at High Temperature. Issue 4 (7th December 2017) - Li, Rongguang; Fu, Guangyan; Xu, Zeren; Su, Yong; Hao, Yongsheng
Abstract : This work investigates texture evolution in an Mg–3Gd–0.2Al alloy during extrusion and after annealing at 500 °C. It shows that the dynamically recrystallized (DRX) grains formed in grain boundaries and twins have different influence on texture evolution. After extrusion, the DRX grains that nucleated at grain boundaries have texture distributing from <20–21> || ED to <11–21> || ED, while these in twins do from <10–12> || ED to <11–22> || ED. After further annealing process, the <11–21> || ED component is strengthened and become the dominating texture component, which results in a strong rare earth (RE) texture. Thus, the RE texture is mainly attributed to the preferential nucleation at grain boundaries during extrusion and the privileged growth of the grains with <11–21> || ED orientation during annealing. Abstract : A trace of {10–11}–{10–12} double‐twin is identified. Orientation of double‐twin is close to <10–12> || ED, and ones of DRX grains range from <10–12> || ED to <11–22> || ED. Thus, DRX grains within twins have orientations close to that of twins.